Generalization of the Carothers equation for linear step growth polymers - Emilio Meaurio (Scientific Reports)
Abstract In the synthesis of linear step-growth polymers molecular weight control is accomplished through the addition of a controlled amount of monomer carrying the functional group B in excess (B-B or H-B types). The Carothers equation is used to calculate average chain lengths. This paper extends the analysis of chain lengths to include the effect of monofunctional monomers carrying the limiting group A (H-A), allowing the systematic analysis of complex systems containing both bifunctional and monofunctional species of any type (A-A, B-B, H-B and H-A). This refinement is particularly relevant for the synthesis of oligomers from systems with complex feed composition.